Impact of height heterogeneity on canopy turbulence. (27th January 2017) - Hamed, A. M.; Sadowski, M. J.; Nepf, H. M.; Chamorro, L. P.
Abstract : The flow development above and within homogeneous and heterogeneous canopies was experimentally studied using particle image velocimetry in a refractive-index-matching channel. The experiments were designed to gain insight into the effect of height heterogeneity on the structure and spatial distribution of the turbulence. The homogeneous model (base case) is constituted of elements of height h arranged in a staggered configuration; whereas the heterogeneous canopy resembled a row canopy and consisted of elements of two heights h_1=h+(1/3)h and h_2=h-(1/3)h alternated every two rows. Both canopies had the same density, element geometry and mean height. The flow was studied under three submergences H/h=2, 3 and 4, where H denotes the flow depth. The experiments were performed at Reynolds number Re_H6500, 11 300 and 12 300 and nearly constant Froude number Fr0.1 . Turbulence statistics complemented with quadrant analysis and proper orthogonal decomposition reveal richer flow dynamics induced by height heterogeneity. Topography-induced spatially periodic mean flows are observed for the heterogeneous canopy. Furthermore, and in contrast to the homogeneous case, non-vanishing vertical velocity is maintained across the entire length of the heterogeneous canopy with increased levels at lower submergence depths. Further alternations were induced in the magnitude and distribution of the turbulent kinetic energy, Reynolds shear stress and characteristics of the canopy mixing layer, evidencing enhanced mixing and turbulent transport for the heterogeneous canopy especially at lower submergence depths. Overall, the results indicate that heterogeneous canopies exhibit greater vertical turbulent exchange at the canopy interface, suggesting a potential for greater scalar exchange and a greater impact on channel hydraulic resistance than a homogeneous canopy of similar roughness density.